Nutrition Education “SAGARI” (Check Your Waist Circumference) as an Attempt to Prevent Adolescents’ Obesity - Megah Stefani; Athiya Fadlina (Media Karya Kesehatan, 2023)
The incidence of obesity at all ages in Indonesia, including adolescents, has increased. Obesity has a negative impact on physical and social health in adolescents. Excessive food consumption and lack of physical activity are risk factors for obesity in adolescents. Based on this urgency, it is necessary to prevent obesity in adolescents. The purpose of this Community Service activity was to increase adolescents’ understanding of the importance of the 4 pillars of balanced nutrition in efforts and to change attitudes by measuring waist circumference regularly to prevent obesity. Increasing knowledge and attitudes to prevent obesity was obtained by providing a Nutrition Education Program named "SAGARI" (Check Your Own Waist Circumference). The program activities included counseling on the 4 pillars of balanced nutrition with lecture method, demonstration for measuring waist and hip circumferences, measuring nutritional status for SMK students consisting of measuring waist circumference (WC) and body mass index (BMI), and providing measuring tape "SAGARI". The results of this activity were an increase in the median knowledge score from 70.00 to 80.00 and an average attitude score from 3.00 to 3.91 related to obesity prevention in adolescents. These results showed that the "SAGARI" nutrition education program can increase students' knowledge and attitudes regarding obesity prevention which is expected to be implemented through daily behavior. Keywords: Balance nutritional, waist circumference, obesity, adolescent, nutritional status.